Pengaruh Inovasi Produk, Brand Awareness, dan Brand Image Terhadap Loyalitas Pelanggan Pada Pengguna Produk Apple di Kota Mataram - Ni Luh Yesilia Sawitri; L. Jatmiko Jati; Putri Amalia Wardi; Lady Faerossa; M. Chothibul Umam Assa’ady (CV. ITTC INDONESIA, 2025)
Currently smartphone features can replace computer functions ranging from komusikasi, online shopping, browsing, and others. In 2024, it is estimated that the number of iphone users in the world will reach 1.46 billion people, this number is equivalent to 18% of the world's population. The number of Iphone users in Indonesia reached 20 million users in the October 2024 period (DataBoks, 2024). The figure shows that people's purchasing decisions on iPhones are high, especially in the Mataram City area. Mataram City is the capital of West Nusa Tenggara province. Mataram City is a city that is the center of industry and the largest economic turnover in West Nusa Tenggara. In Mataram itself many people choose to use the Iphone rather than other brands. The purpose of this study to determine the effect of product innovation, brand awareness, and brand image on customer loyalty Apple products. This study uses quantitative methods with the number of respondents as many as 120 respondents and data processing tools using SPSS 22. The results of this study that the variable product innovation (X1) positive and insignificant effect on customer loyalty (Y). Brand awareness variable (X2) has a positive and significant effect on customer loyalty (Y). Brand image variable (X3) has a positive and significant effect on customer loyalty (Y). Product innovation variables (X1), brand awareness (X2), brand image (X3) have a positive and significant effect simultaneously on customer loyalty (Y).